2022
DOI: 10.3389/fsufs.2022.841386
|View full text |Cite
|
Sign up to set email alerts
|

Home Food Gardening: Benefits and Barriers During the COVID-19 Pandemic in Santiago, Chile

Abstract: The recent COVID-19 pandemic has changed the way people live in an unprecedented way. This includes severe impacts on people's health and wellbeing such as stress, reduced physical activity and loneliness due to confinement. In parallel, people had to find ways to secure their food, with fresh food especially scarce in some regions due to lockdowns and restricted flow of goods. As in previous massive crises, the practice of home food gardening seemed to have increased during this pandemic. Yet we largely do no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 38 publications
0
18
0
1
Order By: Relevance
“…Some studies have indicated that people produced intentions and behaviors ( [5.] , [8.] , [36] , [33] ) and obtained gardening benefits during the COVID-19 pandemic ( [13.]…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have indicated that people produced intentions and behaviors ( [5.] , [8.] , [36] , [33] ) and obtained gardening benefits during the COVID-19 pandemic ( [13.]…”
Section: Introductionmentioning
confidence: 99%
“…However, very few of the participants chose to share visual data, so they were not included, and the research instead relied upon the descriptions the participants gave – as experts of their own lived experiences - of the gardens about which they were talking. Another limitation is that this study did not evaluate the sociodemographic background of the participants or the physical characteristics of their gardens ( Cerda et al, 2022 ). People's involvement with gardens during the pandemic may differ depending on their socioeconomic status ( Cerda et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Another limitation is that this study did not evaluate the sociodemographic background of the participants or the physical characteristics of their gardens ( Cerda et al, 2022 ). People's involvement with gardens during the pandemic may differ depending on their socioeconomic status ( Cerda et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Owning a garden had only predictive potential when it came to plants, suggesting ties of garden owners to their plants (Hands et al, 2018; Head & Muir, 2006). For example, through gardening activity, people interact with and care for plants in their backyards, ultimately forming emotional bonds to their plants (Cerda et al, 2022; Freeman et al, 2012).…”
Section: Discussionmentioning
confidence: 99%